The relationship between family social capital, social media use and life satisfaction in adolescents - Narjes Geraee; Ahmad Ali Eslami; Raheleh Soltani (Tabriz University of Medical Sciences, 2019)
Background: Nowadays, two social phenomena are identified as factors that significantly influence life satisfaction among adolescents: family social capital and social media use. This study aimed to investigate the direct and indirect relationships between family social capital and life satisfaction, and the possible mediating role of social media use between the variables among Iranian adolescents. Methods: In 2018, this cross-sectional study was carried out on 835 adolescents aged from 12to 19, in six high schools of Isfahan, Iran. Data were collected using a validated four-section questionnaire including demographic characteristics (3 items), life satisfaction (5 items), family social capital (31 items) and social media use (4 items) scales. IBM SPSS version 21 statistical software and AMOS version 24 were used to analyze the data. Structural equation modeling was used to assess the fit of model. The significance level of 0.05 was considered for all data analyses. Results: The findings indicated that family social capital and social media use explained 50%of the variance in life satisfaction. Social media use was found with a partial mediating role in the association between family social capital and life satisfaction. Family social capital was the strongest predictor of life satisfaction (β =0.681, P<0.001). The relationship between social media use and life satisfaction was also statistically significant (β =- 0.12, P<0.001). Conclusion: Social media use and family social capital should be considered while investigating the determinants of life satisfaction among adolescents.